Treating Depression with Botulinum Toxin: A Pooled Analysis of Randomized Controlled Trials - Magid, M.; Finzi, E.; Kruger, T. H. C.; Robertson, H. T.; Keeling, B. H.; Jung, S.; Reichenberg, J. S.; Rosenthal, N. E.; Wollmer, M. A. (Pharmacopsychiatry, 2015)
Introduction: Botulinum toxin A (BTA) injection into the glabellar region is currently being studied as a treatment for major depressive disorder (MDD). Here we explore efficacy data of this novel approach in a pooled analysis.Methods: A literature search revealed 3 RCTs on this topic. Individual patient data and clinical end points shared by these 3 trials were pooled and analyzed as one study (n=134) using multiple regression models with random effects.Results: In the pooled sample, the BTA (n=59) and the placebo group (n=75) did not differ in the baseline variables. Efficacy outcomes revealed BTA superiority over placebo: Improvement in the Hamilton Depression Rating Scale or Montgomery-Asberg Depression Rating Scale 6 weeks after baseline was 45.7% for BTA vs. 14.6% for placebo (p<0.0001), corresponding to a BTA response rate of 54.2% (vs. 10.7%) and a BTA remission rate of 30.5% (vs. 6.7%).Discussion: Equalling the status of a meta-analysis, this study increases evidence that a single treatment of BTA into the glabellar region can reduce symptoms of MDD. Further studies are needed to better understand how BTA exerts its mood-lifting effect.
Keywords: botulinum neurotoxin A; meta-analysis; antidepressant; relaxation